2021
DOI: 10.1016/j.idcr.2020.e01022
|View full text |Cite
|
Sign up to set email alerts
|

Cerebro-rhino-orbital mucormycosis and aspergillosis coinfection in a patient with diabetes mellitus: A case report

Abstract: Opportunistic fungal infections are life-threatening conditions with a high rate of morality, mostly occurring in immunocompromised hosts. We reported the case of mixed mold infection in a 69 year-old patient with latent diabetes mellitus. She was initially admitted for right orbital cellulitis. Cerebro-rhino-orbital mucormycosis and aspergillosis coinfection was diagnosed from mycological testing and histology after nasal biopsy sample. The patient received amphotericin B deoxycholate then voriconazole combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Coinfection with mucormycosis and aspergillosis is a rare entity, and very few cases have been published in the literature. Johnson et al [ 18 ] reported a case of combined probable pulmonary aspergillosis and possible mucormycosis in a diabetic male with COVID-19 in the ICU who was treated with liposomal amphotericin B. Zayet et al reported a case of cerebro-rhino-orbital mucormycosis and aspergillosis coinfection in a patient with diabetes mellitus with complete recovery after antifungal therapy combined with surgical debridement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coinfection with mucormycosis and aspergillosis is a rare entity, and very few cases have been published in the literature. Johnson et al [ 18 ] reported a case of combined probable pulmonary aspergillosis and possible mucormycosis in a diabetic male with COVID-19 in the ICU who was treated with liposomal amphotericin B. Zayet et al reported a case of cerebro-rhino-orbital mucormycosis and aspergillosis coinfection in a patient with diabetes mellitus with complete recovery after antifungal therapy combined with surgical debridement [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on fungal co-infections in AIFR. Zayet et al reported a case of cerebro-rhino-orbital mucormycosis and aspergillosis coinfection in a patient with diabetes mellitus with complete recovery after amphotericin B deoxycholate then voriconazole in combination with surgical debridement [ 9 ]. It was assumed that a combination of risk factors, including COVID-19 per se, diabetes mellitus, and corticosteroid treatment, had led to mixed infections in the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…Another target could be Pentraxin 3 (PTX3), which has been shown to be a promising marker for aspergillosis ( Cunha et al, 2014 ). Mucormycosis frequently co-occurs with aspergillosis ( Alfano et al, 2006 ; Tsikala-Vafea et al, 2020 ; Johnson et al, 2021 ; Zayet et al, 2021 ). SNPs in PRRs like Toll-like receptors (TLRs) have already been associated with increased susceptibility to fungal infections ( Bergantim et al, 2013 ; Wang et al, 2013 ; Fischer et al, 2016 ; Zhang et al, 2019 ; Aqsa et al, 2020 ).…”
Section: Current Aspects In Diagnosis and Prediction Of Other Fungal ...mentioning
confidence: 99%